Narrative of the Children's World in the story "The Furious Chornobyl Dog" by E. Gutsalo (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The peculiarities of the narrative of the short story by E. Hutsalo”The Rabid Chornobyl Dog” are being analyzed in the article. By means of distinguishing the dominating forms of narration, types of narrators the peculiar author’s understanding of the children’s world is defined here, of an almost ideal world with its purity, sincerity, exalted spirituality and the ability to protect and save, to understand each other without any words, to value the sincere friendship.
Keywords: narrative; focalization; heterodiegetic extradiegetic narrator; omniscient narrator; author’s image; voices of the characters